Normalized characterization method for fatigue behavior of cement-treated aggregates based on the yield criterion. (20th December 2019) - Liu, Chaochao; Lv, Songtao; Peng, Xinghai; Zheng, Jianlong
Highlights: The yield surface of cement-treated aggregates (CTA) was established. Proposed a normalized characterization method of fatigue based on the yield criterion. Fatigue behavior of CTA was characterized by the normalized characterization method. Abstract: The objective of this paper is to propose a normalized characterization method based on the yield criterion to eliminate the impacts of different stress models on the fatigue behaviors characterization of cement-treated aggregates. Based on the theory of octahedral shear stress strength and yield surface mode, the yield surface of cement-treated aggregates was established with four-point bending, compression, and indirect tensile strength value under different loading rates. Then, the fatigue stress and corresponding ultimate strength could be characterized by the yield surface, uniformly and uniquely. In the yield surface space ( I1, J 2 ), the fatigue stress growth route from initial stress to ultimate strength was identified as fatigue stress path. Based on the fatigue stress path, the fatigue stress ratios related to loading rate and stress model were calculated. With these stress ratios, the conventional S-N fatigue equation was modified, on the basis of which a normalized characterization method of fatigue behavior was proposed to characterize the fatigue behavior of cement-treated aggregates. Compared with the traditional characterized method, the normalized characterization method has considered the influence of loading rate and stress model on strength and fatigue test results. The test results demonstrated that different strength and fatigue test results were obtained under distinct stress model and loading rates. All strength values have been expressed indiscriminately in the yield surface. With the normalized characterization method, a unique fatigue curve was gained for cement-treated aggregates under different loading rates and stress models. Therefore, findings of this work realized the normalization characterization of fatigue behavior of cement-treated aggregates.